Introducing society: A lifelong learning perspective on public libraries’ contribution to integration - Skøtt, Bo (Nordic Journal of Library and Information Studies, 2021)
Public libraries have a societal duty to promote the peaceful coexistence between population and are therefore involved in integration work. However, the question is whether the integration perspective is suitable for addressing current issues or if other perspectives are more adequate. To study this, I conducted a literature review of published articles on Scandinavian public libraries’ integration work, six semi-structured interviews with male asylum seekers and an email interview with the chief operations officer at three asylum reception centres in Denmark. Using a lifelong learning perspective, I was able to consider the six asylum seekers’ experiences with integration in new ways. It became evident how integration is an ambiguous concept, and how the integration process does not constitute temporary phases but rather initiates lifelong learning processes, just like the activities native Danes conducts in their efforts to handle their lives in late modernity. The lifelong learning perspective probably cannot replace the integration perspective, but it may help us understand which activities are appropriate for public libraries to engage in. The public libraries’ task is not to assimilate, but to promote new citizens’ opportunities for peaceful coexistence by facilitating people’s participation in society.